HISTORIOGRAPHY OF ARCHITECTURAL ANALYSIS OF MUHAMMAD TARAGAI ULUGBEK’S SUPREME MADRASAH (American Journal of Research in Humanities and Social Sciences, 2023)
A lot has been said and written about the Mirzo Ulugbek madrasa in Samarkand Registan. Among them, when was this madrasa built (1417-1420), how was the educational process organized, what subjects were taught in the madrasa, how many rooms were there (54), How many students studied (100-110), what scholars worked (Kazizada Rumi, Mirza Ulugbek, Shamsiddin Muhammad Khafavi, Giyasiddin Jamshid Koshi, Alauddin Ali Kushchi and etc.), the patterns on the madrasa facade, the parameters of the madrasa, and similar evidentiary opinions were expressed and debated. done However, until now, only a few scholars G.A. Pugachenkova, P.Sh. Zohidov, K.S. Kryukov and others have paid attention to the analysis of this madrasa-university from an architectural point of view. This article presents valuable information about the historiography of the architectural analysis of Mirzo Ulugbek Supreme Madrasah.